A Proposal That Does Not Advance Our Understanding of Hypnosis - Cardena, Etzel; Terhune, Devin B. (Journal of Scientific Exploration, 2012)
In his paper Hypnosis Reconsidered, Resituated, and Redefined (JSE 26(2):297–327), Adam Crabtree, a distinguished expert in the history of hypnosis, maintains that contemporary hypnosis research suffers from conceptual disorder. In his words, he attempts to redefine hypnosis in order to provide a stronger ground for future research. We find that his proposed reconsideration of hypnosis as a form of “trance” characterized by a focus on internal stimuli and involving the recruitment of appropriate subliminal resources is neither novel nor helpful to our current understanding of hypnosis. Among the problems we find with his paper is that it is conceptually unclear and is not informed by current research and theory; for instance, it disregards well-established findings such as individual differences in responsiveness to hypnosis and the importance of suggestion for the elicitation of hypnotic phenomena. Historical knowledge of a field is invaluable but is alone insufficient to understand its current status or propose pathways for future research and theory. Keywords: hypnosis—trance—suggestion